Effect of hypoglycemic agents with weight loss effect plus a high protein diet and moderate exercise on diabetes remission in adults with obesity and type 2 diabetes: a randomized controlled trial - Shi Zhang; Yi Wang; Xincheng Wang; Mingxin Leng; Renjiao Liu; Zhouhuiling Li; Jing Li; Jixuan Xiao; Dangmin Hou; Xinying Gao; Chunjun Li (BMC Medicine)
Abstract Background This study aimed to explore the effects of hypoglycemic agents with weight loss effect plus a high protein diet and moderate exercise on weight loss and diabetes remission in adults with obesity and newly diagnosed prediabetes/type 2 diabetes (T2D). Methods Participants with obesity and newly diagnosed prediabetes or T2D (n = 61) were randomly allocated to standard treatment group (conventional medication and lifestyle guidance for 12 months) and intensive treatment group (in addition to conventional medication, a high protein diet and moderate exercise were given for 12 months). Results By month 12, 60 (98.4%) participants completed the 12-month follow-up visit. In the intensive treatment group, 73.33% patients in the prediabetes subgroup returned to normoglycemia and the diabetes remission rate was 86.67% in the diabetes subgroup, which were much higher than the remission rate of prediabetes subgroup (7.69%) and diabetes subgroup (16.67%) in the standard treatment group (P < 0.001). The mean weight change was − 19.29 kg (95% CI, − 22.95 to − 15.63) in the intensive treatment group and − 1.52 kg (95% CI, − 5.12 to 2.07) in the standard treatment group from baseline after intervention. The weight change between the two groups was significantly different (net difference, − 17.77 kg; 95% CI, − 22.90 to − 12.64; P < 0.001). Percent of body fat, visceral fat area, and hepatic controlled attenuation parameter value reduced significantly in the intensive treatment group compared to the standard treatment group (P < 0.001). Conclusions Hypoglycemic agents with weight loss effect plus a high protein diet and moderate exercise could lead to a considerable proportion of patients with diabetes achieving diabetes remission. Trial registration chictr.org.cn ChiCTR2100044305.